Association of Lower Adiponectin Plasma Levels, Increased Age and Smoking with Subclinical Atherosclerosis in Patients with HIV-1 Infection - Bellinati, Philipe Q.; Alfieri, Daniela Frizon; Flauzino, Tamires; Junior, Paulo F. G.; Rossi, Diogo Jorge; Breganó, José Wander; Simão, Andrea Name Colado; de Almeida, Elaine Regina Delicato; Lozovoy, Marcell Alysson Batisti; Reiche, Edna Maria Vissoci (Current HIV Research, 2020)
Background: The association between subclinical atherosclerosis and traditional cardiovascular disease (CVD) risk factors, inflammatory and metabolic biomarkers has been demonstrated around the world and specifically Brazilian human immunodeficiency virus type 1 (HIV-1)- infected individuals. However, the association between subclinical atherosclerosis and these aforementioned factors combined with anti-inflammatory biomarkers has not been examined in these populations. Objectives: To evaluate the association of the carotid intima-media thickness (cIMT) with CVD risk factors, inflammatory, metabolic and HIV-1 infection markers combined with adiponectin and interleukin (IL)-10 as anti-inflammatory variables. Methods: In this case-control study, 49 HIV-1-infected patients on combined antiretroviral therapy (cART) and 85 controls were compared for traditional CVD risk factors, inflammatory, metabolic, and anti-inflammatory variables. Further, we compared HIV-1-infected patients according to their cIMT (as continuous and categorized <0.9 or ≥0.9 mm variable) visualized by carotid ultrasonography doppler (USGD). Results: Twenty-four (48.9%) HIV-1-infected patients showed cIMT ≥0.9 mm. The patients had higher levels of C reactive protein on high sensitivity assay (hsCRP), tumor necrosis factor α, IL-6, IL-10, triglycerides, and insulin, and lower levels of adiponectin, total cholesterol and low-density lipoprotein cholesterol than controls (all p<0.05). Low levels of adiponectin were negatively associated with cIMT ≥0.9 mm (p=0.019), and explained 18.7% of the cIMT variance. Age (p=0.033) and current smoking (p=0.028) were positively associated with cIMT values, while adiponectin levels (p=0.008) were negatively associated with cIMT values; together, these three variables explained 27.3% of cIMT variance. Conclusion: Low adiponectin was associated with higher cIMT in HIV-1-infected patients on cART. Low adiponectin levels in combination with age and smoking could explain, in part, the increased subclinical atherosclerosis observed in these patients. Adiponectin may be a good candidate for predicting subclinical atherosclerosis in the management of HIV-1-infected patients in public health care, especially where USGD is not available.
Keywords: carotid intima-media thickness